A Single Nuclease Active Site of the Escherichia coli RecBCD Enzyme Catalyzes Single-stranded DNA Degradation in Both Directions - Wang, Jingdi; Chen, Ruiwu; Julin, Douglas A. (The Journal of biological chemistry, 2000)
The RecBCD enzyme of Escherichia coli is an ATP-dependent DNA exonuclease and a helicase. Its exonuclease activity is subject to regulation by an octameric nucleotide sequence called Ï. In this study, site-directed mutations were made in the carboxyl-terminal nuclease domain of the RecB subunit, and their effects on RecBCD's enzymatic activities were investigated. Mutation of two amino acid residues, Asp 1067 and Lys 1082 , abolished nuclease activity on both single- and double-stranded DNA. Together with Asp 1080 , these residues compose a motif that is similar to one shown to form the active site of several restriction endonucleases. The nuclease reactions catalyzed by the RecBCD enzyme should therefore follow the same mechanism as these restriction endonucleases. Furthermore, the mutant enzymes were unable to produce Ï-specific fragments that are thought to result from the 3â²-5â² and 5â²-3â² single-stranded exonuclease activities of the enzyme during its reaction with Ï-containing double-stranded DNA. The results show that the nuclease active site in the RecB C-terminal 30-kDa domain is the universal nuclease active site of RecBCD that is responsible for DNA degradation in both directions during the reaction with double-stranded DNA. A novel explanation for the observed nuclease polarity switch and RecBCD-DNA interaction is offered.